Microfluidic-assisted preparation of PLGA nanoparticles for drug delivery purposes: experimental study and computational fluid dynamic simulation - Parisa Shokoohinia; Marziyeh Hajialyani; Komail Sadrjavadi; Mona Akbari; Masoud Rahimi; Salar Khaledian; Ali Fattahi (Wolters Kluwer Medknow Publications, 2019)
This study, for the first time, tries to provide a simultaneous experimental and computational fluid dynamic (CFD) simulation investigation for production of uniform, reproducible, and stable polylactic-co-glycolic acid (PLGA) nanoparticles. CFD simulation was carried out to observe fluid flow behavior and micromixing in microfluidic system and improve our understanding about the governing fluid profile. The major objective of such effort was to provide a carrier for controlled and sustained release profile of different drugs. Different experimental parameters were optimized to obtain PLGA nanoparticles with proper size and minimized polydispersity index. The particle size, polydispersity, morphology, and stability of nanoparticles were compared. Microfluidic system provided a platform to control over the characteristics of nanoparticles. Using microfluidic system, the obtained particles were more uniform and harmonious in size, more stable, monodisperse and spherical, while particles produced by batch method were non-spherical and polydisperse. The best size and polydispersity index in the microfluidic method was obtained using 2% PLGA and 0.0625% (w/v) polyvinyl alcohol (PVA) solutions, and the flow rate ratio of 10:0.6 for PVA and PLGA solutions. CFD simulation demonstrated the high mixing intensity of about 0.99 at optimum condition in the microfluidic system, which is the possible reason for advantageous performance of this system. Altogether, the results of microfluidic-assisted method were found to be more reproducible, predictable, and controllable than batch method for producing a nanoformulation for delivery of drugs.